IMPLEMENTASI PENGGUNAAN PENILAIAN PORTOFOLIO DALAM PEMBELAJARAN MENULIS PADA TINGKAT SMK DI KABUPATEN BOGOR - Basuki, Mariani; Lustyantie, Ninuk; Murtadho, Fathiaty (Universitas Muria Kudus, 2024)
The aim of this research is to analyze the implementation of the use of portfolio assessment in learning to write at the vocational school level in Bogor district.The method used in this research is a descriptive qualitative method, as the research subject for teachers and students. The instruments and data collection techniques used consisted of interviews, observation and documentation. The data analysis technique uses the Milles and Huberman model theory which consists of data collection, data reduction, data display and conclusions. The research results show that Bogor district vocational school teachers have used portfolio assessment in writing learning activities. This was obtained from the results of interviews, observations and documents of teachers who had carried out the portfolio assessment stage in learning to write quite well but not yet optimally. There are still several steps that have not been implemented by teachers in the form of obstacles in providing reviews and reflections on students' assignment results due to time constraints.